1998
DOI: 10.1021/jo981153w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of the Intramolecular Reactivity of Free tert-Butylphenylmethylene. Modification of the Chemistry of tert-Butylmethylene by the Introduction of a Phenyl Group

Abstract: The chemistry of tert-butylphenylmethylene, 2, has been investigated experimentally and computationally. Free carbene 2 was generated by the thermal rearrangement of p-tert-butylphenylmethylene and observed to rearrange by C-H insertion to give 1,1-dimethyl-2-phenylcyclopropane, 3, and by C-C insertion to yield 2-methyl-3-phenyl-2-butene, 4. An examination of the 3:4 ratio led to the conclusion that C-H insertion is favored over C-C insertion by 1.6 +/- 0.1 kcal/mol in good agreement with a calculated (PMP2/6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…One of us has previously found that DFT calculations using polarized double-ζ basis sets provide generally excellent agreement with geometries and singlet−triplet energy splittings for carbenes where high-quality gas-phase experimental data are available . Other studies, often involving comparisons of theory to condensed-phase data, have also reported favorably on DFT as applied to carbenes. ,46d,, However, insofar as benchmarking of this level has been done neither for perfluorinated carbenes (other than 1 ) nor for their epoxide cracking reactions, we did examine the quantitative utility of the BPW91/cc-pVDZ level in comparison with other levels of theory that experience suggests might be useful.…”
mentioning
confidence: 99%
“…One of us has previously found that DFT calculations using polarized double-ζ basis sets provide generally excellent agreement with geometries and singlet−triplet energy splittings for carbenes where high-quality gas-phase experimental data are available . Other studies, often involving comparisons of theory to condensed-phase data, have also reported favorably on DFT as applied to carbenes. ,46d,, However, insofar as benchmarking of this level has been done neither for perfluorinated carbenes (other than 1 ) nor for their epoxide cracking reactions, we did examine the quantitative utility of the BPW91/cc-pVDZ level in comparison with other levels of theory that experience suggests might be useful.…”
mentioning
confidence: 99%